An Evaluation of Economic Potential Solar Photovoltaic Farm in Thailand: Case study of Polycrystalline Silicon and Amorphous Silicon Thin Film - Suphahitanukool, Chaiporn; Hunsacharoonroj, Issaree; Usapein, Parnuwat; Khedari, Joseph; Waewsak, Jompob; Hirunalbh, Jongjit (International Journal of Energy Economics and Policy, 2018)
Solar energy in Thailand plays an important role to achieve the target of the Alternative Energy Development Plan (AEDP). Enormous investments from investors are expected to occur for support AEDP. Therefore, the objective of this study was to evaluate and compare the economic potential of solar PV farm between polycrystalline silicon (PCSS) and amorphous silicon thin film (ASTF) type. Questionnaires submitted to private solar PV farm for collecting data. As a result, four main investment costs of PSS are identified: (1) photovoltaic module; (2) connection system; (3) inverter, and (4) engineering construction, distributed as 58.09%, 19.66%, 12.96%, and 4.47%, respectively. The financial analysis found that Payback period (PB), Internal Rate of Return (IRR), and Solar Plant capital of ASTF were less than PCSS; however, it returns low income along 25 years than PCSS. It could be suggested that the investment on PCSS is worth than ASTF. Keywords: Economic potential, Solar PV farm, Investment, Financial economic. JEL Classifications: C8, G0, M2